TASAWUF DIKALANGAN PENDIDIK MUHAMMADIYAH KABUPATEN PANDEGLANG - Agung Soleh Rahayu; Naf’an Tarihoran (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2014)
Muhammadiyah as an Islamic purification movement hold of all forms of heresy and superstition, but many educators in the development of Muhammadiyah who learn and follow certain taswuf so that the relationship of Sufism and Muhammadiyah were initially positioned facing into position in line . This study descript that educators Muhammadiyah Pandeglang district formalize Sufism because they think are often diverted into a congregation with ritual practices are very strict. In Muhammadiyah no tawasulan, yasinan, tahlilan or manaqiban. But the practice of Sufism and Dhikr accepted by them into individual practices, with the aim to improve the ideal morality. Muhammadiyah educators strongly encourage their students to increase voluntary prayer, dhikr and wird, and move forward in a sincere attitude.